Promising Sb2(S, Se)3 Solar Cells with High Open Voltage by Application of a TiO2/CdS Double Buffer Layer. Issue 11 (11th September 2018) - Wang, Weihuang; Wang, Xiaomin; Chen, Guilin; Chen, Binwen; Cai, Huiling; Chen, Tao; Chen, Shuiyuan; Huang, Zhigao; Zhu, Changfei; Zhang, Yi
Abstract : Sb2 (S, Se)3 has gathered a lot of attention recently as a promising alternative absorber material. However, the efficiencies of Sb2 (S, Se)3 devices are seriously restricted by the low open circuit voltage ( V oc ). In this work, Sb2 (S, Se)3 devices equipped with a TiO2 /CdS double buffer layer are prepared by a hydro‐thermal method, which aims to overcome the V oc deficit. The obtained average V oc of the devices is 785 mV and the champion efficiency of 5.73% is also achieved with a highest V oc = 792 mV, Jsc = 12.03 mA cm −2, FF = 60.9%. The improvement of V oc is benefited from the reduced band gap offset after application of the double buffer layer. The non‐encapsulated device could keep an average power conversion efficiency of 5.69% after being stored in ambient air over a month. This indicates the great potential of a double buffer layer in new chalcogenide photovoltaic devices. Abstract : The efficiencies of Sb2 (S, Se)3 devices are restricted by the low open circuit voltage ( V oc ). In this work, Sb2 (S, Se)3 devices equipped with a TiO2 /CdS double buffer layer are prepared by a hydro‐thermal method. The champion efficiency of 5.73% is achieved with a highest V oc of 792 mV. The remarkable lifting of the V oc proves the great potential of a double buffer layer in new chalcogenide photovoltaic devices.